Microparticles containing erlotinib-loaded solid lipid nanoparticles for treatment of non-small cell lung cancer. (3rd August 2017) - Bakhtiary, Zahra; Barar, Jaleh; Aghanejad, Ayuob; Saei, Amir Ata; Nemati, Elhameh; Ezzati Nazhad Dolatabadi, Jafar; Omidi, Yadollah
Abstract: Non-small cell lung cancer (NSCLC) patients with sensitizing mutations in the exons 18–21 of the epithelial growth factor receptor (EGFR) gene show increased kinase activity of EGFR. Hence, tyrosine kinase inhibitors (TKIs) such as erlotinib (ETB) have commonly been used as the second line therapeutic option for the treatment of metastatic NSCLC. While the ETB is available as an oral dosage form, the local delivery of this TKI to the diseased cells of the lung may ameliorate its therapeutic impacts. In the current study, we report on the development of ETB-loaded solid lipid nanoparticle (SLN) based formulation of dry powder inhaler (ETB-SLN DPI). ETB-SLNs were formulated using designated amount of compritol/poloxamer 407. The engineered ETB-SLNs showed sub-100 nm spherical shape with an encapsulation efficiency of 78.21%. MTT assay and DAPI staining revealed that the ETB-SLNs enhanced the cytotoxicity of cargo drug molecules in the human alveolar adenocarcinoma epithelial A549 cells as a model for NSCLC. To attain the ETB-SLN DPI, the ETB-SLNs were efficiently spray dried into microparticles (1–5 μm) along with mannitol. The ETB-SLN DPI powder displayed suitable flowability and aerodynamic traits. The Carr's Index, Hausner ratio and Next Generation Impactor (NGI) analyses confirmed deep inhalation pattern of the formulation. Based on these findings, we propose the ETB-SLN DPI as a promising treatment modality for the NSCLC patients.